2021
DOI: 10.1093/hmg/ddab290
|View full text |Cite
|
Sign up to set email alerts
|

FUS-induced neurotoxicity is prevented by inhibiting GSK-3β in aDrosophilamodel of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS)-linked mutations in fused in sarcoma (FUS) lead to the formation of cytoplasmic aggregates in neurons. They are believed play a critical role in the pathogenesis of FUS-associated ALS. Therefore, the clearance and degradation of cytoplasmic FUS aggregates in neurons may be considered a therapeutic strategy for ALS. However, the molecular pathogenic mechanisms behind FUS-associated ALS remain poorly understood. Here, we report GSK-3β as a potential modulator of FUS-induced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…Notably, loss of function of sgg has been shown to rescue neuronal dysfunction in a TDP-43 Drosophila model 16,51 . Moreover, our findings are in line with Choi et al, who recently suggested that sgg inhibition could rescue various phenotypes in Drosophila overexpressing human FUS 52 . PP2A is a multi-subunit phosphatase highly expressed in the brain, of which PP2A-C (mts) is the catalytic subunit.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, loss of function of sgg has been shown to rescue neuronal dysfunction in a TDP-43 Drosophila model 16,51 . Moreover, our findings are in line with Choi et al, who recently suggested that sgg inhibition could rescue various phenotypes in Drosophila overexpressing human FUS 52 . PP2A is a multi-subunit phosphatase highly expressed in the brain, of which PP2A-C (mts) is the catalytic subunit.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, loss-of-function of sgg has been shown to rescue neuronal dysfunction in a TDP-43 Drosophila model [ 58 , 69 ]. Moreover, our findings are in line with Choi et al, who recently suggested that sgg inhibition could rescue various phenotypes in Drosophila overexpressing human FUS [ 10 ]. PP2A is a multi-subunit phosphatase highly expressed in the brain, of which PP2A-C (mts) is the catalytic subunit.…”
Section: Discussionsupporting
confidence: 92%
“…In line with this, recent findings by Xu et al [92] demonstrate the strong implication of the Wnt/β-Catenin signalling pathway in cadmium-induced developmental neurotoxicity and neuroinflammation. GSK3B is involved in neurotoxicity induced by kainic acid [93] and FUS [94] and in TDP-43-mediated neurotoxicity [95].…”
Section: Common Proteins Involved In Temperature-induced Neurotoxicitymentioning
confidence: 99%